A double-peaked Lyman-α emitter with a stronger blue peak multiply imaged by the galaxy cluster RXC J0018.5+1626. Issue 1 (1st August 2022) - Furtak, Lukas J; Plat, Adèle; Zitrin, Adi; Topping, Micheal W; Stark, Daniel P; Strait, Victoria; Charlot, Stéphane; Coe, Dan; Andrade-Santos, Felipe; Bradač, Maruša; Bradley, Larry; Lemaux, Brian C; et al.
ABSTRACT: We report the discovery of a double-peaked Lyman-α (Ly α) emitter (LAE) at z = 3.2177 ± 0.0001 in VLT/MUSE data. The galaxy is strongly lensed by the galaxy cluster RXC J0018.5+1626 recently observed in the RELICS survey, and the double-peaked Ly α emission is clearly detected in the two counter images in the MUSE field of view. We measure a relatively high Ly α rest-frame equivalent width (EW) of EWLy α, 0 = (63 ± 2) Å. Additional spectroscopy with Gemini /GNIRS in the near-infrared (NIR) allows us to measure the H β, [O iii ] λ4959 Å, and [O iii ] λ5007 Å emission lines, which show moderate rest-frame EWs of the order of a few ∼10–100 Å, an [O iii ] λ5007 Å/H β ratio of 4.8 ± 0.7, and a lower limit on the [O iii ]/[O ii ] ratio of >9.3. The galaxy has very blue UV-continuum slopes of βFUV = −2.23 ± 0.06 and βNUV = −3.0 ± 0.2, and is magnified by factors μ ∼ 7–10 in each of the two images, thus enabling a view into a low-mass ($M_{\star }\simeq 10^{7.5}\, M_{\odot }$ ) high-redshift galaxy analogue. Notably, the blue peak of the Ly α profile is significantly stronger than the red peak, which suggests an inflow of matter and possibly very low H i column densities in its circumgalactic gas. To the best of our knowledge, this is the first detection of such a Ly α profile. Combined with the high lensing magnification and image multiplicity, these properties make this galaxy a prime candidate for follow-up observations to search for LyC emission and constrain the LyC photon escape fraction.